(untitled) (ENTHYMEMA, 2014)
Ideas in literature are immersed into a huge mass of non-conceptual discourses; take very often a metaphoric form; they are in many texts entrusted to fictional persons, to imaginary characters; they have a specific, and even paradoxical, form of responsibility. These features of ideas in literature, making them a privileged object of study in intellectual history, are exemplified by Théophile Gautier’s novel Mademoiselle de Maupin, more precisely by its preface, considered to be a manifesto of Art for Art’s Sake doctrine.